2020
DOI: 10.1002/app.50006
|View full text |Cite
|
Sign up to set email alerts
|

Platinum cross‐linked chitosan hydrogels synthesized in water saturated with CO2 under high pressure

Abstract: The creation of biocompatible composite hydrogels from renewable biopolymers with stabilized functional platinum nanoparticles seems to be an important scientific task. The formation of such hydrogels in a unique medium of carbonic acid under high pressure CO 2 is promising due to its sterilizing ability under pressure, biocompatibility after decompression and environmental friendliness. In the present work, stable chitosan hydrogels with platinum nanoparticles were obtained in such solutions. The hydrogel nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Presumably, most of cupric ions were deposited on the fibers in the form of a thin uniform nanolayer, and it can be concluded that the presence of chitosan on polypropylene fibers actually stabilizes the deposition and growth of cupric ion structures. We believe that amino‐ and hydroxyl‐groups of chitosan are responsible for the stabilizing interaction with cupric ion through chelation/complexation 25,26 . Indeed, according to the theory of hard and soft acids and bases, amino groups can be considered as ligands that have a greater affinity for transition metal cations 36 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Presumably, most of cupric ions were deposited on the fibers in the form of a thin uniform nanolayer, and it can be concluded that the presence of chitosan on polypropylene fibers actually stabilizes the deposition and growth of cupric ion structures. We believe that amino‐ and hydroxyl‐groups of chitosan are responsible for the stabilizing interaction with cupric ion through chelation/complexation 25,26 . Indeed, according to the theory of hard and soft acids and bases, amino groups can be considered as ligands that have a greater affinity for transition metal cations 36 …”
Section: Resultsmentioning
confidence: 99%
“…We believe that amino-and hydroxyl-groups of chitosan are responsible for the stabilizing interaction with cupric ion through chelation/complexation. 25,26 Indeed, according to the theory of hard and soft acids and bases, amino groups can be considered as ligands that have a greater affinity for transition metal cations. 36 An EDS analysis was performed to confirm that the adsorbate on the fibers visible in the SEM images was indeed copper-containing one (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another advantage of this medium is that the product formed in such a system is not contaminated with any traces of solvents, since the CO 2 spontaneously self-eliminates after decompression, while the resulting product remains in the water. Previously, chitosan solutions in the presence of carbonic acid have been used to develop composites based on chitosan and silver, platinum, and gold nanoparticles [ 38 , 39 , 40 ], but the possibilities of composites structure and form modification were not explored. It is also worth noting that copper is a transition metal, that differs somewhat from noble ones in its properties, which is why a detailed review of the characteristics of gels based on copper and chitosan is quite useful.…”
Section: Introductionmentioning
confidence: 99%